Trend Peralihan Artis Televisi Menjadi Youtube Content Creator - Elsa Maghfira Paramesti; Syifa Syarifah Alamiyah; Fitrania Yunsafa Cahayani (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2021)
Youtube is one of the social media that is currently trending and provides space for everyone to convey their creative ideas. Youtube also provides feedback in the form of Adsense for content creators who have interesting videos and are seen by many people. This study discusses students' perceptions of the trend of transitioning television artists into youtube content creators. The purpose of this study was to determine students' perceptions of the transition from television artists to youtube content creators. This research method uses qualitative research with audience analysis. The results of this study indicate that students' perceptions of the transition from television artists to YouTube content creators are natural, especially supported by increasingly advanced information technology. It provides an opportunity for everyone as a means to develop soft skills. Meanwhile, the uploaded content must have good value and quality, so that it can get appreciation from many people. Besides that, the perspective of students in accessing information and entertainment prefers YouTube, because it is more effective and practical to reach audiences in a short time.